The Bahamas : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that The Bahamas' real GDP is estimated to have expanded by 1.3 percent in 2017. Economic activity has been supported by the completion of Baha Mar, new foreign direct investment-financed projects, and post-hurricane reconstruction activity. However, air tourist arrivals declined 4 percent in 2017, reflecting the impact of Hurricane Matthew on hotel infrastructure in the Grand Bahama Island. Real GDP growth is projected at 2.5 percent in 2018 and 2.25 percent in 2019 on the back of stronger growth in the United States; the phased opening of Baha Mar; and a pickup in foreign direct investment. Medium-term growth is projected to remain at 1.5 percent, reflecting significant structural impediments.